Hosting the Small Island Developing States: Two Scenarios - Vaha Milla Emilia (Emerald Insight, 2022)
-
-
Purpose: It has been estimated that some Small Island Developing States might have only decades before their territories become uninhabitable. Future of these states poses timely questions to world politics. The purpose of this paper is to examine the relationship between the potential hosts and endangered states at the time of relocation by looking at two relocation scenarios: Kiribati/New Zealand and the Maldives/Sri Lanka.
Design/methodology/approach: The paper uses normative international political theory to explore the nature of relocation. It critically examines the proposal for the free right to choose the new host state. Guided by two examples, the paper proposes that we should not ignore the contingent reasoning when evaluating these hypothetical scenarios.
Findings: The paper argues that the endangered state might have ethical grounds for its rights–claims to continuous existence on a chosen territory. At the same time, both scenarios looked at here also impose serious constraints. By illustrating these constraints, the paper aims at mapping some central challenges that the continuity of endangered states creates to international state-system. The paper argues that the complex relationships between the potential hosts and the relocating communities should not be ignored.
Originality/value: This paper provides a contextual analysis of two hypothetical relocation scenarios. In doing so, it relies on comparative research in two regions and offers a normative argument in relation to the rights of both endangered and host populations.
-